Analysis Of Employee Performance At Ma'had Al Ayman Arabic Language And Islamic Education Foundation - Dani Sudiwan* (Riwayat: Educational Journal of History and Humanities, 2023)
In an Islamic Education Foundation, the success and progress obtained cannot be separated from the existing tools, both management systems and employee performance. Many people view the completeness of facilities as the only factor that brings success in the foundation. The employees are only treated as supporting elements and used as workers. Ma'had Al-Ayman Arabic Language and Islamic Education Foundation is one of the Islamic education foundations in Pontianak City that has not maximized the potential of its employees. The study entitled "Analysis of Employee Performance at Ma'had Al-Ayman Arabic Language and Islamic Education Foundation" was conducted to assess how existing employees are performing. The procedures used in this study are qualitative procedures and are collected by interviewing and observation procedures after that the data is processed by data analysis and editing. There are also those who illustrate research are functional employees and teaching staff. The purpose of this research is to analyze employee performance, find out the factors that affect employee performance and find out how the performance management system at the Arabic Language Foundation and Islamic Education Ma'had Al-Ayman Pontianak. From this study, it is known that the performance of existing employees has not been maximized and many of the employees whose quality of work, quantity, effectiveness, and teamwork are still not good.